Correction: Molecular Heterogeneity of Ewing Sarcoma as Detected by Ion Torrent Sequencing. - Nana Zhang; Guanjun Yue; Yan Zhang; Jiangfeng You; Hua Wang (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0153546.].